Challenges of Ovarian Cancer Patient and Caregiver Online Health Information Seeking. Issue 1 (13th October 2021) - Chi, Yu; Hui, Vivian; Kunsak, Hannah; Brusilovsky, Peter; Donovan, Heidi; He, Daqing; Lee, Young Ji
Abstract: Ovarian cancer (OvCa) patients and caregivers have constant and evolving information needs. To meet their needs, they seek information from various resources, including online health information. Although about 60% of cancer patients are now using the Internet to meet their information needs, little is known about online health information seeking (OHIS) among OvCa patients and caregivers. To address this gap, we interviewed 18 OvCa patients and 2 family caregivers of OvCa patients and conducted content analysis on the transcribed data. We identified three challenges of OHIS: (1) lack of OvCa‐related knowledge, (2) poor quality of online information, and (3) inherent characteristics of OvCa, such as the high complexity and aggressive progression of the disease. The findings deepen the understanding of OvCa patients and caregivers and provide insights to better support their OHIS experience.